A MODULE ON ISLAMIC-BASED PARENTING EDUCATION FOR YOUTH FAMILY DEVELOPMENT: EDUCATING MUSLIM TEENAGERS FOR FUTURE SUCCESS - Kosim, Muhammad; Kustati, Martin; Nasution, Ilman; Anidar, Jum; Amelia, Rezki; Febriani, Suci Ramadhanti (Islam Futura, 2024)
This project aims to create an Islamic-centered parenting education module implemented in Youth Family Guidance (Bina Keluarga Remaja - BKR) programs to help parents educate and equip their teenagers for future success. The module was created by gathering parenting education resources for teenagers from an Islamic viewpoint that align with the current content in BKR activities. The Islamic content is incorporated into all BKR operations. The module was developed using the three stages of the Plomp model: preliminary study, prototype development, and assessment. This research has resulted in an Islamic-centered parenting module called "How to Educate Muslim Teenagers in Reaching the Future". The validators deemed the module very valid and practical after testing. The module has been partially implemented and feedback from observers and informants suggests that it can effectively enhance parents' comprehension and abilities in educating and caring for adolescent children during BKR activities.